2017
DOI: 10.3892/etm.2017.4914
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid B and danshensu induce osteogenic differentiation of rat bone marrow stromal stem cells by upregulating the nitric oxide pathway

Abstract: The aim of the present study was to investigate the effect of salvianolic acid B (Sal B) and danshensu (DSU) on the osteogenic differentiation of bone marrow mesenchymal stem cells (MSCs) and the mechanisms of the effects. The osteogenic differentiation of MSCs in culture was assessed by measuring alkaline phosphatase (ALP) activity, osteocalcin (OCN) production, nitric oxide (NO) production and the mRNA expression levels of osteoprotegerin (OPG) and its ligand by MSCs. MSCs were successfully induced to differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Danshensu, rutin, isoquercitrin, ferulic acid, hesperidin, rosmarinic acid, and salvianolic acid B were shown to attenuate OVX or RANKL-induced bone loss in vivo ( Horcajada-Molteni et al, 2000 ; Chiba et al, 2003 ; Sassa et al, 2003 ; Lee et al, 2015 ; Qu et al, 2016 ; Liu and Shen, 2018 ; Fayed et al, 2019 ). In addition, danshensu, rutin, isoquercitrin, ferulic acid, hesperidin, rosmarinic acid, salvianolic acid B, and linarin were observed to promote osteoblast differentiation ( Huan-qiong and Liao, 2008 ; Trzeciakiewicz et al, 2010 ; Li et al, 2016 ; Du et al, 2017 ; Zhang et al, 2017 ; Li et al, 2019 ; Jeong et al, 2021 ; Liu et al, 2021 ). Thus, these findings suggest that the beneficial effects of these phytochemicals may account for the anti-osteoclastogenic and anti-osteoporotic effects of WEMA.…”
Section: Resultsmentioning
confidence: 99%
“…Danshensu, rutin, isoquercitrin, ferulic acid, hesperidin, rosmarinic acid, and salvianolic acid B were shown to attenuate OVX or RANKL-induced bone loss in vivo ( Horcajada-Molteni et al, 2000 ; Chiba et al, 2003 ; Sassa et al, 2003 ; Lee et al, 2015 ; Qu et al, 2016 ; Liu and Shen, 2018 ; Fayed et al, 2019 ). In addition, danshensu, rutin, isoquercitrin, ferulic acid, hesperidin, rosmarinic acid, salvianolic acid B, and linarin were observed to promote osteoblast differentiation ( Huan-qiong and Liao, 2008 ; Trzeciakiewicz et al, 2010 ; Li et al, 2016 ; Du et al, 2017 ; Zhang et al, 2017 ; Li et al, 2019 ; Jeong et al, 2021 ; Liu et al, 2021 ). Thus, these findings suggest that the beneficial effects of these phytochemicals may account for the anti-osteoclastogenic and anti-osteoporotic effects of WEMA.…”
Section: Resultsmentioning
confidence: 99%
“…Throughout the effect of active ingredients from Chinese herbal medicine on stem cells, the following points can be summarized: (1) the botanical source of these active ingredients is Chinese herbal medicines with the characteristics of “Tonifying-Qi,” “Tonifying-Kidney,” and “Tonifying-Blood,” which are often used to treat aging-related diseases; (2) the same active ingredient induces stem cells to differentiate into different tissue cells; although the active ingredients are different, the signal pathways through which they act are similar; (3) the same active ingredient may require different auxiliary conditions in the differentiation of different tissue cells; for example, salvianolic acid B stimulates differentiation into cardiomyocytes that requires vitamin C or TGF β , which is not necessary to differentiate into osteoblasts; (4) several studies have confirmed that there are crosstalk and integration among Wnt, Shh, Notch, and other signaling pathways in regulating stem cell differentiation; for example, salvianolic acid B activated Wnt signaling but prevented Notch signaling when promoting the differentiation of embryonic stem cells into hepatocytes [ 57 ]; salvianolic acid B also activated the Shh signaling pathway and promoted functional recovery and neurogenesis in neuroprotection [ 74 ]; during the promotion of osteoblast differentiation, the function of salvianolic acid B was also involved in nitric oxide-cGMP pathway [ 97 ]; (5) Wnt, Shh, and Notch are not only signal pathways of stem cell differentiation but also important factors of cell senescence. As shown in Table 1 and Figures 1 – 4 , the targeted cells and activated pathways of active ingredients of Chinese herbal medicine are summarized.…”
Section: Discussionmentioning
confidence: 99%
“…Incubation of cells with curcumin resulted in a dose-dependent increase in intracellular nitrite and elevated levels of intracellular cGMP [ 96 ]. Additionally, salvianolic acid B also showed similar effects in inducing nitric oxide production during osteogenic differentiation [ 97 ]. Treatment with ginkgolide B and salidroside resulted in cell proliferation, angiogenesis, and differentiation of BMSCs-EPCs; enhanced the ability of EPCs to integrate into vascular networks; and activated Akt phosphorylation and NO production [ 21 , 25 ].…”
Section: Signaling Pathways In Stem Cell Differentiation Activatedmentioning
confidence: 99%
“…In vivo, Sal B inhibited glucocorticoid-induced osteopenia. It enhanced bone thickness and bone mass by increasing the expression of BMPs, ALP activity, and collagen type I [ 194 , 195 ]. A pilot study in a rat tibia fracture model revealed that treatment with Sal B led to an enhancement in callus growth, histological scores, and post-fracture ALP activity, thus, accelerating early-stage fracture [ 196 ].…”
Section: Natural-compound-based Treatments For Oa Therapymentioning
confidence: 99%